젊은 유방암 환자의 자녀 특성에 따른 양육 스트레스, 양육 행동 및 부모교육 요구도 - 조옥희(Cho, Ok-Hee); 유양숙(Yoo, Yang-Sook); 서영진(Suh, Young-Jin) (Sŏngin Kanho Hakhoe chi, 2011)
Purpose: This study was designed to explore the parental stress, behaviors and need for parental education of young women with breast cancer and how these variables are related to their children characteristics. Methods: The subjects were 110 young women with breast cancer who have a child. Data were collected using questionnaire of parenting stress, parental behaviors and need for parental education. Results: The subjects reported many unmet needs for parental education, and have the highest level of need for education related to breast cancer. Women with daughters have higher level of need for parental education compared to subjects with sons. There was a negative correlation between parenting stress and parental behaviors and between parenting stress and need of parental education. Conclusion: As these results, the development and application of parental education program for mothers with breast cancer in the future should be considered with the demographic characteristics, the social and cultural environment, parenting stress, and parental behaviors of parents and children.